PENGARUH TEKNIK PENILAIAN dan METODE BELAJAR TERHADAP PEMAHAMAN METAKOGNISI BIOLOGI (Eksperimen pada SMA Negeri di Kota Bekasi) - Ahmad Fauzan (Jurnal Inovasi Pendidikan dan Sains, 2020)
Abstract: Research aims to analyse and test hypothesized truth about the influence of assessment techniques and methods of learning towards the understanding of biological sciences. Research hypotheses tested include: 1) there is a significant influence on methods of learning in biological skills. 2) There is a significant influence on the technique of assessment of biological skills. 3) There is a significant influence of interaction between assessment techniques and methods of learning to the ability of biological sciences. Research is conducted by experimental methods. The population is a grade X student of SMA Negeri in Bekasi City with a large sample of 80 students, with sampling techniques used i.e. simple random sampling. The research instrument used is an understanding test of the essay form as much as 10 questions that have been tested for homogeneity with the great χ2count < χtable (4,46 < 7.81). Analyze data using analysis of variance (ANOVA) two paths or directions. Hypothesis testing results obtained the following conclusions: 1) There is a significant influence of methods of learning to the ability of biological metacognisi it is evidenced by Sig. 0.000 < 0.05 and Fh 27,715. 2) There is a significant influence on the technique of assessment of the ability of biological engineering, it is evidenced by Sig. 0.000 < 0.05 and Fh 17,478. 3) There is a significant influence of interaction between assessment techniques and methods of learning to the ability of biological sciences is evidenced by the Sig. 0.048 < 0.05 and Fh 4.052. The results of this research are useful to improve the quality of learning and assessment so as to optimize the understanding of biological knowledge at high school level. Keywords: metacognition, protista, assessment techniques, learning methods.